The Design of Reform Packages Under Uncertainty - Dewatripont, Mathias; Roland, Gérard (American Economic Review, 1993)
The authors present a model of large-scale economic reforms, modeled on the transition process in Eastern Europe, with aggregate and individual uncertainty concerning the outcome of reforms. The government is assumed to choose the speed and sequencing of reforms. The authors compare big-bang strategies with gradualist reform packages. They show that gradualist reform packages may be easier to get started, optimal sequencing of reforms should aim at creating constituencies for further reforms, and gradualism may generate a higher investment response because of a lower option value of waiting than would a big-bang approach. Copyright 1995 by American Economic Association.